2018
DOI: 10.2478/aiht-2018-69-3085
|View full text |Cite
|
Sign up to set email alerts
|

Antimycobacterial potential of the juniper berry essential oil in tap water

Abstract: Mycobacterium avium complex-related diseases are often associated with poorly maintained hot water systems. This calls for the development of new control strategies. The aim of this study was to investigate the activity of essential oils (EOs) from the Mediterranean plants, common juniper, immortelle, sage, lavandin, laurel, and white cedar against Mycobacterium avium ssp. avium, Mycobacterium intracellulare, and Mycobacterium gordonae in culturing broth and freshwater as their most common habitat. To do that,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 38 publications
1
20
0
1
Order By: Relevance
“…Nonetheless, compounds of the other classes, such as monoterpenes hydrocarbons and oxygenated monoterpens, can also play an active role and synergistically contribute to the biological activity of juniper berries EOs (Glišić et al, 2007). Using transmission electron microscopy, Peruč et al (2018) confirmed the inhibitory effect of juniper EO against Mycobacterium spp. by revealing significant morphological changes in the cell membrane and cytoplasm, and leakage of intracellular material.…”
Section: Antimicrobial Activitymentioning
confidence: 87%
“…Nonetheless, compounds of the other classes, such as monoterpenes hydrocarbons and oxygenated monoterpens, can also play an active role and synergistically contribute to the biological activity of juniper berries EOs (Glišić et al, 2007). Using transmission electron microscopy, Peruč et al (2018) confirmed the inhibitory effect of juniper EO against Mycobacterium spp. by revealing significant morphological changes in the cell membrane and cytoplasm, and leakage of intracellular material.…”
Section: Antimicrobial Activitymentioning
confidence: 87%
“…In our previous study (11) time-kill curves of M. avium, M. intracellulare, and M. gordonae in sterile tap water (STW) showed that juniper EO applied at half the minimal effective concentration reduced bacterial counts by approximately 3 log 10 over 24 h and complete inhibited NTM growth after 48 h.…”
Section: Discussionmentioning
confidence: 99%
“…", Zagreb, Croatia. The same batch had already been used in our earlier studies, which show their chemical composition (11,18,19).…”
Section: Essential Oilsmentioning
confidence: 99%
See 1 more Smart Citation
“…EU H. italicum s područja Hrvatske prema dosad dostupnim istraživanjima uobičajeno ima visok sadržaj α-pinena, γ-i α-kurkumena, α-i β-selinena i neril acetata 17,19,33 . Kako je α-pinen bio dominantna komponenta i EU-a plodova borovice (Juniperus communis) čiji smo učinak prema NTM-u testirali u prethodnom istraživanju, smatrali smo da je upravo ta komponenta odgovorna za antimikobakterijski učinak 36 . Međutim kada smo testirali izolirani α-pinen, njegova MIK vrijednost bila je tri puta veća od EU-a borovice i dva puta veća od EU-a smilja, što govori u prilog tezi da komponente eteričnog ulja djeluju sinergistički.…”
Section: Uvodunclassified